Antibacterial efficacy of Citrus hystrix (makrut lime) essential oil against clinical multidrug-resistant methicillin-resistant and methicillin-susceptible Staphylococcus aureus isolates - Preeyaporn M. Sreepian; Panthip Rattanasinganchan; Apichai Sreepian (Elsevier, 2023)
The increasing incidence of methicillin-resistant S. aureus is a major public health concern. Recently, the performance of Citrus hystrix essential oil (CHEO) has been shown to contain broad-spectrum antibacterial activity. Therefore, this study aims to determine the antibacterial activity of CHEO alone and in combination with gentamicin against panels of clinical isolates of methicillin-susceptible S. aureus (MSSA, n = 45) and methicillin-resistant S. aureus (MRSA, n = 40). Antibiotic susceptibility testing revealed multidrug-resistant (MDR) patterns among 3 MSSA isolates and 39 MRSA isolates, indicating that the clinical MRSA isolates were associated with MDR (p < 0.05). For the drug resistant isolates, resistance was observed toward most antibiotics, except for chloramphenicol, trimethoprim-sulfamethoxazole, linezolid, and vancomycin. Antibacterial screening by disk diffusion demonstrated that CHEO alone had certain antibacterial activity toward all MSSA isolates (IZD: 16.0 ± 4.7 mm) and MRSA isolates (IZD: 16.5 ± 4.2 mm) (p > 0.05). The MIC values of CHEO are 18.3 ± 6.1 mg/mL in MSSA isolates and 17.9 ± 6.9 mg/mL in MRSA isolates (p > 0.05). The antibacterial activity of CHEO demonstrated the bactericidal effect with MIC index 1.0-1.4. Time-killing kinetics revealed that CHEO at 1 × MIC completely killed MSSA and MRSA within 12 h. Moreover, the checkerboard titration demonstrated the synergistic and additive interactions of CHEO with gentamicin with FIC index 0.012-0.625. CHEO against human epidermal keratinocyte; HaCaT cell line demonstrated the IC50 value at 2.15 mg/mL. The use of CHEO as an alternative antibacterial agent would reduce the emergence of resistant bacteria, especially MDR MRSA.